Archiving ethnography? The impossibility and the necessity - David Zeitlyn (Ateliers d'Anthropologie)
I review the conflicting injunctions to archive and not to archive anthropological field materials (data). There are ethical contradictions: some ethics codes tell us to destroy data after a period of time, others to save for the long term. I discuss the responsibilities researchers have to different groups of people and how these may conflict. I illustrate beneficial long-term uses of field data from my own work with Mambila people in Cameroon and Nigeria, partly using archival material in ways never originally intended (so never considered for consent). To adhere strictly to some data management protocols would result in inhumane and I suggest unethical action. We must accept that life is contradictory and find ways of managing this: long term embargoes might provide a solution that is workable, although difficult to implement with digital archives.